Exploring the factors contributing to parent stress symptoms during the COVID‐19 pandemic in Europe: An ABC‐X model approach - Anis Ben Brik (19239442) (2024)
The COVID‐19 pandemic has had a significant impact on the mental health and well‐being of families worldwide, with parents particularly at risk for stress and other psychological symptoms. In this study, we sought to understand the factors contributing to parent stress symptoms during the early stages of the pandemic in 23 European countries (N = 40,138) using the double ABC‐X model. We examined whether the relationship between stressor pile‐up and perceived stress was mediated by family satisfaction and relationship satisfaction and whether family resiliency beliefs impacted these mediated relationships. Our results showed a direct association between stressor pile‐up and parent stress symptoms, but we did not find evidence for the mediating role of family satisfaction or relationship satisfaction in this relationship. We also found that family resiliency beliefs did not moderate the indirect effects of family satisfaction and relationship satisfaction on parent stress symptoms. These findings suggest that the ABC‐X model may not fully capture the processes affecting parents' experience of stress during the pandemic and that alternative models such as the vulnerability‐stress‐adaptation model may be more relevant. Future research should also consider the potential negative impact of resiliency beliefs on mental health and other risk and protective factors such as self‐compassion. Other Information Published in: Family Process License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/famp.13063